2500-year cultural sequence in the Massim region of eastern Papua New Guinea reflects adaptive strategies to small islands and changing climate regimes since Lapita settlement. (July 2020) - Shaw, Ben; Coxe, Simon; Kewibu, Vincent; Haro, Jemina; Hull, Emily; Hawkins, Stuart
Islands present significant technological and ecological challenges for long-term human settlement, with archaeological investigations of islands globally able to shed light on the adaptive plasticity of cultural groups to changing climatic regimes. The Massim islands of eastern New Guinea significantly reduced in size throughout the Holocene (⩽11.7 kya), providing a unique opportunity to investigate the long-term adaptive capabilities of humans to changing island ecosystems. Here, we report a 2500-2300 year cultural sequence on Nimowa Island in the Louisiade Archipelago of the Massim region which began with the arrival of a late Lapita population during initial beachfront development. Sediment analyses indicate earlier settlement on the island would not have been possible as the coastline was unstable until near-modern sea levels were reached. The island was abandoned from 1290 to 530 cal. BP during a period of unusually dry conditions ('Medieval Climate Anomaly') and probable freshwater shortages. Re-settlement coincided with wetter climatic conditions ('Little Ice Age'), associated with the establishment of large villages, the earliest expression of local pottery traditions and the onset of large-scale regional exchange networks. Import of non-local obsidian reflects two pulses of interaction followed by periods of increased isolation. With the absence of high-quality lithic resources, shell, coral and bone were used as a locally available alternative for tool production. Increased cyclone frequency from ~500 cal. BP greatly increased beach volume in the island and coastal New Guinea, which facilitated the movement of populations onto smaller islands. A late prehistoric shift in settlement patterns had a profound impact on regional social dynamics.